Case report: STRN3-NTRK3 fusion in uterine sarcoma with spleen metastasis: a new variant in the spectrum of NTRK-rearranged tumors - Colombo, Piergiuseppe; Buonamassa, Giuseppina Adriana; Giulianini, Anita; Hassan, Letizia; Rudini, Noemi; Rizzo, Antonio; Cavallo, Enrico; Carnaghi, Carlo; Goudarzi, Salumeh; Mongiovì, Sebastiano; Pafumi, Sarah; Marletta, Stefano (Frontiers in Medicine, 2024)
Neurotrophic tyrosine receptor kinase (NTRK) fusions are infrequent genetic events that can occur in various tumor types. Specifically, NTRK-rearranged sarcoma has been observed in pediatric mesenchymal tumors and, to a lesser extent, in adult mesenchymal tumors like fibrosarcoma. Recently, NTRK-rearranged uterine sarcoma (US) has been identified as a rare entity characterized by constitutive activation or overexpression of the TRK receptor, which plays a role in cell proliferation and differentiation. Since its initial description in 2018, only 46 cases of NTRK-rearranged US have been reported. In this context, herein we describe an exceptional case of an STRN3::NTRK3 fused US with histologically confirmed splenic metastasis. Notably, such localization has not been previously associated with pure uterine sarcomas in the literature. The fusion involved STRN3 (exon-3) and NTRK3 (exon-14) genes and was identified through next-generation sequencing analysis. Recognizing this specific molecular rearrangement is crucial, as it not only enables targeted therapy but also holds diagnostic significance in specific clinical scenarios.